2017
DOI: 10.1186/s12884-017-1479-1
|View full text |Cite
|
Sign up to set email alerts
|

Institutional maternal and perinatal deaths: a review of 40 low and middle income countries

Abstract: BackgroundUnderstanding the magnitude and clinical causes of maternal and perinatal mortality are basic requirements for positive change. Facility-based information offers a contextualized resource for clinical and organizational quality improvement. We describe the magnitude of institutional maternal mortality, causes of death and cause-specific case fatality rates, as well as stillbirth and pre-discharge neonatal death rates.MethodsThis paper draws on secondary data from 40 low and middle income countries th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 23 publications
6
55
2
1
Order By: Relevance
“…Obstetric hemorrhage, severe pre-eclampsia and eclampsia, postpartum sepsis and obstructed labor have been shown as the leading direct causes of maternal death in countries from sub-Saharan Africa [17,21,25]. This is consistent with the findings in our study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Obstetric hemorrhage, severe pre-eclampsia and eclampsia, postpartum sepsis and obstructed labor have been shown as the leading direct causes of maternal death in countries from sub-Saharan Africa [17,21,25]. This is consistent with the findings in our study.…”
Section: Discussionsupporting
confidence: 93%
“…Several studies carried out in Ethiopia have pointed to a changing trend in the distribution of causes of maternal death [15][16][17][18][19][20][21]. In 2014 a systematic review revealed that the major causes of maternal death were obstructed labor/uterine rupture (36%), hemorrhage (22%), hypertensive disorders of pregnancy (19%) and sepsis/infection (13%) [22].…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by our results in which for one‐third of all screened cases, anemia was an underlying reason and in those identified as near‐misses a mortality index of 8% and 6% in Tanzania and Uganda respectively, was observed. An interesting finding of the present study was the large number of ectopic pregnancies identified; the mortality index was low in ectopic pregnancy as reported elsewhere …”
Section: Discussionsupporting
confidence: 78%
“…An interesting finding of the present study was the large number of ectopic pregnancies identified; the mortality index was low in ectopic pregnancy as reported elsewhere. 27 The present study has both strengths and limitations. A large number of primary and secondary level facilities adhering to the same implementation principles were included, the standard WHO nearmiss tool was used, and the study was conducted in a similar way in the two settings, Tanzania and Uganda.…”
Section: Proportion Of Complications Per Reported Deliveries (%)mentioning
confidence: 92%
“…In sub-Saharan Africa, obstetric haemorrhage accounted for 24.5% of maternal deaths [2]. Extrauterine gestation is a key contributor and accounts for approximately 7% of mortalities due to obstetric haemorrhage and 2% of maternal mortalities in low and middle income countries [3]. Most cases of extrauterine gestation are not picked up early prior to rupture in low resource countries [4] [5] [6] [7].…”
Section: Introductionmentioning
confidence: 99%